Compliance of Venous Thromboembolism (VTE) Assessment in Older Adult Inpatient Unit - Rosy Purakayastha; Bassem Elsayed (BJPsych Open)
Aims: Venous Thromboembolism (VTE) is a preventable condition that significantly contributes to morbidity and mortality in hospitalized patients. In psychiatric inpatient settings, VTE incidence ranges from 2–12%, with a rate of 1.5 per 1000 admissions within the first three months of hospitalization. The National Institute for Health and Care Excellence (NICE) guidelines recommend that all mental health inpatients, including those on psychiatric wards, should undergo a VTE risk assessment upon admission. The aim of this project was to assess compliance with these guidelines in the Older Adult Ward at East-Mid Surrey (The Meadows).